β-glucans from Agaricus bisporus mushroom products drive Trained Immunity - Case, Sarah; O'Brien, Tara; Ledwith, Anna E.; Chen, Shilong; Horneck Johnston, Cian J. H.; Hackett, Emer E.; O'Sullivan, Michele; Charles-Messance, Hugo; Dempsey, Elaine; Yadav, Supriya; Wilson, Jude; Corr, Sinead C.; et al. (Frontiers in Nutrition, 2024)
Macrofungi, such as edible mushrooms, have been used as a valuable medical resource for millennia as a result of their antibacterial and immuno-modulatory components.Mushrooms contain dietary fibres known as b-glucans, a class of polysaccharides previously linked to the induction of Trained Immunity. However, little is known about the ability of mushroom-derived b-glucans to induce trained immunity. Using various powdered forms of the white button mushroom (Agaricus bisporus), we found that mouse macrophages pre-treated with whole mushroom powder (WMP) displayed enhanced responses to restimulation with TLR ligands, being particularly sensitive to Toll-like receptor (TLR)-2 stimulation using synthetic lipopeptides. This trained response was modest compared to training observed with yeast-derived b-glucans and correlated with the amount of (bio-available) b-glucans in the WMP. Enriching for b-glucans content using either a simulated in-vitro digestion or chemical fractionation retained and boosted the trained response with WMP, respectively. Importantly, both WMP and digested-WMP preparations retained b-glucans as identified by nuclear magnetic resonance analysis and both displayed the capacity to train human monocytes and enhanced responses to restimulation. To determine if dietary incorporation of mushroom products can lead to Trained Immunity in myeloid cells in vivo, mice were given a regimen of WMP by oral gavage prior to sacrifice. Flow cytometric analysis of bone-marrow progenitors indicated alterations in hematopoietic stem and progenitor cells population dynamics, with shift toward myeloid-committed multi-potent progenitor cells. Mature bone marrow-derived macrophages derived from these mice displayed enhanced responses to restimulation, again particularly sensitive to TLR2. Taken together, these data demonstrate that bglucans from common macrofungi can train innate immune cells and could point to novel ways of delivering bio-available b-glucans for education of the innate immune system.